Criminal Law in Myanmar - CHAN, Wing Cheong (Institutional Knowledge at Singapore Management University, 2023)
A commentary on the Myanmar Penal Code that describes and critically evaluates the general principles of criminal responsibility contained in the Code. This book was originally published in English in 2016. It was republished in Burmese in 2023.